Evidence for plasmid DNA exchange after polyplex mixing. Issue 33 (27th July 2016) - Pigeon, L.; Gonçalves, C.; Pichon, C.; Midoux, P.
Abstract : When interacting with one another, a polyplex self-assembly of DNA with a cationic polymer made using the same DNA and the same polymer can be unpackaged by aggregation or collapse and then the exchange of DNA can occur during the new DNA/polymer assembly. Abstract : The self-assembly of a plasmid DNA (pDNA) with cationic polymers or cationic liposomes forms nanosized supramolecular structures called lipoplexes, polyplexes and lipopolyplexes. Here, we report that when two polyplex preparations made using the same polymer and the same pDNA but labelled with two different fluorophores are mixed together, pDNA molecules are exchanged. Indeed, when Flu-pDNA complexed with histidinylated lPEI (Flu-pDNA/His-lPEI) polyplexes are mixed with Cy5-pDNA complexed with histidinylated lPEI (Cy5-pDNA/His-lPEI) polyplexes, a high quantity of polyplexes emitting dual fluorescence is observed and FRET indicates that one single polyplex contains two kinds of fluorescent pDNA molecules. This phenomenon depends on the polymer-type and the strength of the pDNA/polymer interaction. No exchange is observed with polylysine polyplexes, caged His-lPEI polyplexes, lipoplexes, lipopolyplexes or when His-lPEI polyplexes are mixed with lipoplexes. Our results suggest that aggregation or collapse of polyplexes occurs after their interaction leading to their unpackaging followed by the formation of new polyplexes with the exchange of pDNA.